Five new species of the genus Leucania Ochsenheimer in Central America (Lepidoptera: Noctuidae) - Mccabe, Timothy L.; Adams, Morton S. (Zootaxa, 2023)
Five new species of the noctuid genus Leucania in Central America are described: L. mopan Adams and McCabe, sp. nov., L. merga Adams and McCabe, sp. nov., L. championi Adams and McCabe, sp. nov., L. colorada McCabe and Adams, sp. nov., L. sororia McCabe and Adams, sp. nov. The internal genitalia are key to resolving the taxonomy in this genus; in particular, the morphology of the male everted endophallus (vesica) and the female bursa copulatrix jointly resolve taxonomic confusion among cryptic species near L. albifasciata, L. oaxacana and L. humidicola. We recognize the valvular pore plate and the “poma” (bubble-like structure at base of valvae) as generic synapomorphies for Leucania. Lappets (inflatable pouches on the outer aspect of the valvae) are newly described. Descriptions and color illustrations of the imagos, male valvae, everted endophalli, and the female bursae copulatrix are provided for all newly described species and selected congeners to aid identification. Additional nomenclatorial actions are: Leucania complicata Strecker, 1898 rest. stat.; Leucania februalis Hill, 1924 syn. nov., a junior synonym of L. humidicola; Leucania elephas Troubridge 2020 syn. nov., a junior synonym of L. humidicola.